Ansible : from basics to guru. (Complete video course, 2022)
13+ Hours of Video Instruction 13+ hours of video instruction teaching you how to get started with Ansible for managing Linux, Windows, Containers, Network Devices, and Cloud. Ansible is the leading solution for configuration management. It lets you automate assets in an environment--including Linux, Windows, Cloud, Network Devices and more--and works as an application-deployment tool enabling infrastructure as code. Ansible Complete Video Course: From Basics to Guru will teach Ansible from the ground up, so whether you're a novice or an experienced developer, administrator or user, this title will help you get the most out of your Ansible solutions and playbooks and manage your heterogeneous environment. This course consists of all the major and popular topics and concepts that are relevant to Ansible. It begins with the basics of Ansible and how to get started. It will then explore how to develop flexible playbooks before jumping managed infrastructure, ad-hocs commands, Ansible Tower, conditionals, plugins, and managing containers among various other important topics. Every lesson contains multiple practical examples that show how Ansible is used in the real world. At the end of each lesson, you will find an exercise that was built so you can practice your skills; each exercise also comes with a video explanation. Ansible Complete Video Course: From Basics to Guru is also a deep-dive into the topics covered in the Red Hat Ansible best practices exam (EX447). Topics include Getting Started with Ansible Developing Flexible Playbooks Advanced Ansible Management Managing Heterogenous Environment with Ansible About the Instructor Sander van Vugt has many years of experience working with, writing about, and teaching Linux and Open-Source topics. He is the author of the best-selling Red Hat RHCSA and RHCE Cert Guides as well as a number of other titles on Kubernetes (including CKAD and CKA), Ansible, Containers, Bash, Microservices and more. Sander also works as a Linux and DevOps instructor, teaching onsite and online classes for customers around the world. Skill Level Beginner to Intermediate Learn How To Manage IT infrastructure with Ansible by following examples Get started with Ansible in just a few hours Get a feel for Ansible before focusing on Ansible Certification exams Perform advanced tasks with Ansible Who Should Take This Course Developers and administrators who want to use Ansible to manage different assets in their IT environment. IT users and professionals that want to get experience with simple programming languages. Course Requirements A minimum of 3 virtual machines, running Red Hat Enterprise Linux or Rocky Linux One virtual machine running the latest Ubuntu LTS Optionally, the following can be added One virtual machine running Windows Administrator Access to AWS Administrator Access to Azure A Cisco network device A virtual machine running VMware ESXi About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.